The impact of fringe benefits on job satisfaction at DEMC Specialist Hospital Shah Alam, Selangor / Nur Amalina Rafe and Nur Arina Ismail Nasiruddin - Rafe, Nur Amalina; Ismail Nasiruddin, Nur Arina (2014)
This research is about a study on the impact of fringe benefits towards job satisfaction that has chosen the employees of DEMC Specialist Hospital as respondents. This research was to determine that there is a significant impact of the fringe benefits on job satisfaction. The sampling frame is the supporting employees of DEMC Specialist Hospital with population of 131 employees and by using stratified random sampling technique, 97 respondents were made as sample size. The unit of analysis is individual with the instrument of Likert Scale questions and close-ended questions. Questionnaire is used to collect the data and IBM SPSS Statistics 20 data software analysis is used to compute the regression of the variables. This research should make a contribution to the understanding of the impact of fringe benefits on job satisfaction for most private organizations in any industries, human resource practitioners and employees themselves. The result of the research shows that the one variable which is health protection is significantly influence the job satisfaction and the hypothesis is accepted.